On the Privatisation of Academic Writing Development: A Post-EATAW 2017 Provocation - Neculai, Catalina (Journal of Academic Writing, 2018)
All across continental Europe and the United Kingdom, academic writing teaching or development is slowly becoming part and parcel of existing institutional frameworks intended to enhance student writing and professional research communication. While more and more universities are investing in such infrastructures of support internally, a relatively new phenomenon is also consolidating: the steady rise of privatised, for-profit writing development businesses that draw their client base from academic institutions. Prompted by EATAW 2017, the conference organised at Royal Holloway, University of London, this think piece raises some fundamental questions regarding the privatisation of academic writing development and invites colleagues to consider its assumptions, emergence and implications in their local, higher education contexts.